SIMFONI NILAI PERUSAHAAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Eugenia, Angellica; Apriwenni, Prima (Universitas Multimedia Nusantara, 2025)
Abstract – The study focuses on explaining the factors that affect company value. The dependent variable used is company value, while the independent variables are Net Profit Margin, leverage, and company size. The secondary data used in this research were obtained from the annual financial reports of 59 manufacturing companies listed on the Indonesia Stock Exchange (IDX) website from 2021 to 2023, yielding a total of 177 data points. The analysis was conducted using the Multiple Regression Analysis method with SPSS 26. The results of this research show that Net Profit Margin has a positive and significant effect on company value. Leverage also has a positive and significant effect on company value. However, the results do not support a positive and significant effect of company size on company value. These findings suggest that profitability and leverage are important factors in enhancing firm value, while company size may not necessarily influence investor perception or market valuation in the context of manufacturing firms during the study period. Keywords: Company Value; Net Profit Margin; Leverage; Company Size